Pharmacokinetic profile of alniditan nasal spray during and outside migraine attacks - Roon, K I (Blackwell Science Inc, 1999)
AIMS: To compare the pharmacokinetic profile of intranasal alniditan during and outside migraine attacks, and to investigate the relationship between initial rise of alniditan plasma concentration, and headache improvement. METHODS: Twenty-seven migraine patients (age: 18–65 years) were randomized to receive alniditan 2 mg or 4 mg, and investigated both during and outside a migraine attack. Maximal plasma concentrations (C(max)), time to C(max) (t(max)), and the area under the curve over 2 h (AUC(0,2 h)), were calculated from the individual plasma concentration-time profile, obtained from 10 blood samples in each patient, during each of the two administrations. RESULTS: Alniditan was rapidly absorbed into the systemic circulation (t(max) = 11min). All investigated pharmacokinetic parameters (C(max), t(max), AUC(0,2 h)) were similar during and outside migraine attacks, both in the 2 mg (n = 13) and the 4 mg group (n = 14). In the 4 mg group, during attacks, mean plasma alniditan concentration at 5 min after administration (C(t = 5)) in responders (21±16 ng ml(−1); n = 10) was significantly higher than the C(t = 5) in nonresponders (3±3 ng ml(−1); P = 0.01; n = 4). However, the C(max) and AUC(0,2 h) in responders (33±18 ng ml(−1) and 12±6 ng ml(−1) h) were also significantly higher than the C(max) and AUC(0,2 h) in nonresponders (13±9 ng ml(−1); P = 0.048 and 5±3 ng ml(−1) h; P = 0.03). CONCLUSIONS: Absorption of alniditan nasal spray was not affected by migraine attacks, although 95% confidence intervals were wide. Early rise of plasma concentrations and the amount of drug in the circulation were related to headache improvement in the higher dose group.